2021
DOI: 10.1002/edn3.249
|View full text |Cite
|
Sign up to set email alerts
|

The amount of environmental DNA increases with freshwater crayfish density and over time

Abstract: Over the last years, the analysis of environmental DNA (eDNA) has become an important approach to investigate species communities. Due to its non‐invasive nature and high sensitivity, this method is excellently suited to monitor the occurrence of endangered or invasive species. Native freshwater crayfish are threatened across Europe. Due to their nocturnal activity and hidden lifestyle, crayfish monitoring is difficult and time consuming with conventional methods. Thus, eDNA‐based monitoring of native, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…The huge increase (> 1000 fold) in eDNA concentrations in the high-density tanks with non-fed crayfish at 10 °C might be explained by injuries from aggressive interactions (Sint et al 2021) combined with the relatively clean water with assumingly low microbiological activity. In a similar tank experiment, Dunn et al (2017) successfully detected eDNA of P. leniusculus, but only established a significant relationship between eDNA concentration and crayfish biomass when female crayfish were ovigerous.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The huge increase (> 1000 fold) in eDNA concentrations in the high-density tanks with non-fed crayfish at 10 °C might be explained by injuries from aggressive interactions (Sint et al 2021) combined with the relatively clean water with assumingly low microbiological activity. In a similar tank experiment, Dunn et al (2017) successfully detected eDNA of P. leniusculus, but only established a significant relationship between eDNA concentration and crayfish biomass when female crayfish were ovigerous.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our findings and those of Dunn et al (2017), Harper et al (2018) observed an increase in eDNA concentration when comparing tanks with one and three P. leniusculus. Additionally, Sint et al (2021) 2021) took multiple samples up to 59 hours after the crayfish had been added to the tanks, the sampling in our experiment and that of Dunn et al (2017) was conducted after seven and eleven days, respectively. This could have led to a state of saturation or equilibrium where eDNA is emitted from crayfish at a similar rate to its degradation by microbial activity (Barnes et al 2014;Salter 2018;Saito and Doi 2021), thus obscuring any differences between the tested factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…eDNA studies in terrestrial environments have conventionally involved collection of targeted specimens, such as animal residues left on trees, fecal deposits, or samplings from hoof or paw prints in earth or snow 26,27 , hampering widespread application. However, the challenge of sampling terrestrial environments is currently being reassessed by the transformative discovery that the DNA of animal, insect, and non-anemophilous plants can be reliably recovered from filtered air samples [28][29][30][31][32] . In a notable study conducted at the Copenhagen Zoo 28 , Clare et al showed that airborne eDNA could be collected in a localized manner and analyzed to disclose specific species within a defined geographical radius.…”
Section: Ecological Arenasmentioning
confidence: 99%
“…eDNA has been widely applied for both aquatic and terrestrial species detection in a variety of ecological contexts. As discussed below, in aquatic samples from lotic environments, eDNA density increases with species density and biomass, although the relationship is not linear 29,30 . Although data from head-to-head comparisons are limited, several studies suggest that eDNA performs favorably compared with conventional gold-standard methods, and may in some cases produce superior results.…”
Section: Species Detection and Biomass Analysismentioning
confidence: 99%